1935
DOI: 10.1002/hlca.193501801143
|View full text |Cite
|
Sign up to set email alerts
|

Flavinphosphorsäure aus Leber

Abstract: Das Flavin tler Lebw (Rind) fintlet sich nach B. 0. BirZ~r iintl BdZer') grijsstenteils in hochmolekularer, nicht dialysierb;nw Form in diesem Organ Tor. Die genannten Autoren schiitzen den hochmolekulnren Anteil auf '70-80 % rles Gesamtflavingehaltes. Das f r e i e Flavin der Leber haben P. KC/YW)*, H . Salomo)~ ixntl Ir'. Rchiipp') vor einiger Zeit in krystallisierter und reiner Form isoliert. Es wurrlen hierbei aus 80 kg trockenem Leberextrakt, eritsprechend ca. 300 kg Frischleber, aber nur SS mg nnalysenr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1937
1937
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…1 Tables 2 and 3), which is consistent with the findings of Koeppe & Miller (1972) and Arron & Edwards (1979). We have previously considered the possibility that the pH-dependence of NADPH oxidation is linked to the protonation of the 2'-phosphate group a), which has a pK of 6.2-6.3 (Theorell, 1935). Such an effect has been observed with lactate dehydrogenase (Navazio et al, 1957).…”
Section: Kinetics Of Nadph Oxidationsupporting
confidence: 85%
“…1 Tables 2 and 3), which is consistent with the findings of Koeppe & Miller (1972) and Arron & Edwards (1979). We have previously considered the possibility that the pH-dependence of NADPH oxidation is linked to the protonation of the 2'-phosphate group a), which has a pK of 6.2-6.3 (Theorell, 1935). Such an effect has been observed with lactate dehydrogenase (Navazio et al, 1957).…”
Section: Kinetics Of Nadph Oxidationsupporting
confidence: 85%
“…It has previously been shown that "N NMR techniques yield useful information about the structure and electronic properties of free and protein-bound flavins [15,17,[29][30][31], In the case of flavins a correlation between the chemical shift of the I5N nuclei and their n-electron density seems to exist [23,291. Accordingly the resonances of pyridinc-type nitrogens " (1) and N(5) in the oxidized flavin] and of pyrrole-type nitrogens " (3) and N(10) in the oxidized flavin] have different properties. In the case of pyridine-type nitrogens the lone-pair electrons are orthogonal to the aromatic system, whereas in the case of pyrrole-type nitrogens the lone-pair electrons participate in the aromatic system of the heterocycle.…”
Section: ' ' N N M R Sludics On Old Yellow Cwzymementioning
confidence: 99%
“…It was isolated by Warburg and Christian in 1932 from brewer's yeast [I, 21. The prosthetic group of the protein was identified as F M N by Theorell [3] (for an overview on the protein see [4]). The protein consists of two subunits of about 49 kDa, each containing one molecule of FMN.…”
mentioning
confidence: 99%
“…Al ipoxygenase is abundant in soybean seeds (SBL1) and it has been studied from early days of protein chemistry. [1] It is almostc olorless as isolated. Beginningw ith the earliest structures of lipoxygenases, ac avity with dimensions suitable for binding af attya cid, winding through ab undle composed largely of helices, has been apparent.…”
Section: Overview Of the Active Site In Lipoxygenase And Epr Studiesmentioning
confidence: 99%